New Literacies of Online Research and Comprehension - Leu, Donald J.; Kiili, Carita; Forzani, Elena; Zawilinski, Lisa; O'Byrne, W. Ian; McVerry, J. Greg (The Encyclopedia of Applied Linguistics, 2021)
This entry explores the question of how to conceptualize literacy as a deictic concept, one that continually changes as new technologies for literacy and learning emerge. It suggests a dual-level conceptualization of theory: a New Literacies theory as an overarching theory that encompasses perspectives and findings from the many studies of literacy, which are referred to as new literacies theories, using lower case. It then focuses special attention on an important lower-case theory, the new literacies of online research and comprehension. This new literacies theory frames online reading as a process of problem-based inquiry involving the new skills, strategies, dispositions, and social practices that take place as we use the Internet to solve problems and answer questions. Current understanding of online reading to learn from a New Literacies perspective is informed by recent research using assessments that measure students' ability to conduct online research in science and comprehend what they read in a virtual online world. Findings suggest that online reading requires different skills than reading paper materials; that differences across modes of reading are important for school learning; and that the Internet is best conceived as a literacy issue rather than a technology issue.
Keywords: Literacy; Literacy Practices Online; New Literacies; Online Reading; Teaching Reading; dept.cur

Applied qualitative data analysis after the ontological turn - Marn, T.M.; Wolgemuth, J.R. (Qualitative Report, 2021)
In this article we demonstrate the use and usefulness of new materialism as an analytic lens in applied qualitative inquiry. Intended as a possible entry point to applied inquiry after the ontological turn, we draw on Barad's agential realism to analyze three existing transcripts of focus groups conducted with healthcare workers, traditional birth attendants, and mothers to explore the postnatal care referral behavior of traditional birth attendants in Nigeria. We describe elements of our data analysis process including deep reading, summoning of the inquiry, delaying the inquiry, attuning to glowing data, and writing. We explore how the research phenomenon enacted agential cuts that distinguished participants (healthcare workers, traditional birth attendants, and mothers) and relayed their participation in the focus group. We show how the inclusion of the mothers' babies and the transcripts themselves made available some understandings at the possible exclusion of others. Our Baradian, new materialist analysis shows the inextricability of interview materials (things) and language (discourse) and demonstrates that all applied research is bounded and affected by its material conditions. As a point of entry, we hope our illustration sensitizes applied qualitative researchers to how research decisions, research materials, and research cultures produce what can be known and lived within and beyond the research encounter. © 2021 Nova Southeastern University. All rights reserved.
Keywords: dept.cur; peer-reviewed

From Leaders to Accomplices: Autoethnography as Praxis in Teacher Education - Powell, Jessica (Re-Imagining Transformative Leadership in Teacher Education, 2021)
This is the third and final book in the series Transformative Pedagogies in Teacher Education. Like the first two books in the series it is geared towards practitioners in the field of teacher education. This third book focuses on transformative leadership in teacher education. In other words, the kind of leadership and practices that will be important and necessary to bring about the kind of changes that both teachers and students seek to improve educational outcomes for all students, but in particular Black, Indigenous and racialized students who have been traditionally underserved by the education system. Teacher leadership plays an important role in transformative educational change that challenges all forms of oppression and white supremacy. This book features chapters by a collection of scholars, teacher educators, researchers, teacher advocates and practitioners drawing on their research and experiences to explore critical issues in teacher education. The book will be useful to teacher educators working with teacher candidates in different contexts, experienced teachers and school leaders. Given demographic shifts and the need for educators to respond to growing diversity in schools, educators will find valuable strategies in Transformative Pedagogies in Teacher Education: Re-Imagining Transformative Leadership in Teacher Education they can employ in their own practice. In addition to valuable strategies, authors explore different approaches and perspectives critical in these changing and challenging times. Critical notions of education are posited from different perspectives and contexts. This book will be useful for teacher education programs, principal preparation programs, in-service teachers, school boards and districts engaging in ongoing professional development of teachers and school leaders.
Keywords: Education / Leadership; Education / Professional Development; Education / Teaching Methods & Materials / Social Science; dept.cur

On the sidelines of what works: scientifically based indifference - Wolgemuth, Jennifer R.; Marn, Travis M.; Sabnis, Sujay (International Journal of Research & Method in Education, 2021)
A team of systematic reviewers successfully completed a government-commissioned review of ‘what works to improve post-school outcomes for youth with disabilities’ in 2012. Despite its success, interviews with 10 review team members revealed dissatisfaction with the process and indifference to its outcomes. The purpose of our analysis was to examine how the systematic review process itself led to review team members’ feelings of indifference, resignation, and pessimism. Drawing on the writings of Henry Giroux, Gert Biesta, and Hanna Arendt that warn of the death of democracy and the rise of totalitarianism, we explored how the systematic review certification process, examinations, rules, and structures deadened democratic deliberation and critique necessary, we argue, to conducting good educational science. We end with a call for systematic reviews in education whose researchers, products, and processes remain ethically oriented to keeping democracy alive. © 2021 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: dept.cur; peer-reviewed